RANCANG BANGUN SISTEM REKOMENDASI DESTINASI WISATA DI BALI - Dwi Putra Githa; Singgih Putri, Desy Purnami (LPPM STMIK STIKOM Indonesia, 2019)
Bali is one of the provinces in Indonesia which is famous for its tourism. Bali is visited by many tourists both local and foreign tourists because it is famous for its culture and natural beauty. The problem experienced by tourists is the difficulty in determining the tourism objects to be visited in accordance with the wishes of these tourists. Difficulty in determining tourism objects is caused by limited information about tourism objects in Bali. The tourist destination recommendation system in Bali can be a solution to provide information about tourism objects in Bali and can provide recommendations on tourism objects to be visited according to the criteria entered by the user. This system is a geographic information system that can provide location information and routes to tourism objects chosen by users. This system is created using the concept of mobile web, so that each device is able to use the system only with a web browser. This system was built using the PHP programming language and MySQL database. Based on the tests that have been done, the system has been running according to its function.